The BrEasT cancer afTER-CARE (BETTER-CARE) programme to improve breast cancer follow-up: design and feasibility study results of a cluster-randomised complex intervention trial - Horn, Anna; Wendel, Julia; Franke, Isabella; Bauer, Armin; Baumeister, Harald; Bendig, Eileen; Brucker, Sara; Deutsch, Thomas M.; Garatva, Patricia; Haas, Kirsten; Heil, Lorenz; Hügen, Klemens; et al. (Trials, 2024)
The risk of breast cancer patients for long-term side effects of therapy such as neurotoxicity and cardiotoxicity as well as late effects regarding comorbidities varies from individual to individual. Personalised follow-up care concepts that are tailored to individual needs and the risk of recurrences, side effects and late effects are lacking in routine care in Germany. We describe the methodology of BETTER-CARE, a parallel-arm cluster-randomised controlled trial conducted at 15 intervention and 15 control centres, aiming to recruit 1140 patients, and the results of the pilot phase. The needs- and risk-adapted complex intervention, based on existing development frameworks, includes a multidisciplinary network and digital platforms for symptom and need documentation and just-in-time adaptive interventions. The control group comprises usual care according to clinical guidelines. The primary outcome is health-related quality of life (EORTC QLQ-C30 global health), and secondary outcomes include treatment adherence. The 2-month pilot phase comprising 16 patients in one intervention and one control pilot centre demonstrated the feasibility of the BETTER-CARE approach. BETTER-CARE is a feasible intervention and study concept, investigating individualised needs- and risk-adapted breast cancer follow-up care in Germany. If successful, the approach could be implemented in German routine care. German Clinical Trial Register DRKS00028840. Registered on April 2022.
BETTER-CARE Study Group: Dr. Cordula Müller
Gesehen am 22.05.2025